Eufemisme dalam Surat Kabar Kompas Edisi Oktober 2024 dan Relevansinya dalam Pembelajaran Bahasa Indonesia di SMA - Agustyowati, Diah Rahma Cahya; Firmani, Sakinah Isna; Hidayati, Fathul (Indo-MathEdu Intellectuals Journal, 2024)
In addition to using standard language, the Kompas newspaper also uses special terms or certain words to replace words or things that are considered rude. The language used to replace other terms to sound more subtle is euphemism. This study aims to describe the linguistic form of euphemism in Kompas newspaper and its relevance in Indonesian learning in high school. The type of research used is qualitative research that is descriptive. The data taken in this study are in the form of words and phrases in which there is an element of euphemism. The source of data for this research is the October 2024 edition of the Kompas letter. The data collection technique in this study is the look and record technique. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The study results showed that there were four words and seven phrases that contained euphemisms. Words containing euphemisms are in the form of basic words and affixed words and are in the form of verbs, adjectives, and nouns. Words and phrases containing euphemisms are used to produce and reduce the negative impression of the meaning or meaning of the actual words and phrases. The study results also have relevance to Indonesian language learning in high school and can be associated with learning outcomes in phase F for grade XI.